Relationship between aerobic and anaerobic capacity and cycling time trials - Schwindling, S.; Skorski, S.; Hammes, D.; Meyer, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Cyclists can maintain high velocities during a 40 km race and are still able to perform a great endspurt (Abbiss & Laursen, 2008). It can be assumed that this requires aerobic endurance capacity and a good anaerobic capacity. Both properties can be measured using standardized laboratory tests (e. g. VO2max, lactate thresholds, 30-s anaerobic Wingate test (WIN)). However, studies analysing the relationship between those "classic" cycling tests and actual TT performance are still missing. Hence, the aim of the current study was to determine the relationship between aerobic as well as anaerobic parameters and the 40 km TT performance. Methods: 23 male cyclists (28.8±7.6y) participated in the study. Subjects completed a flat 40 km TT, a WIN and a graded cycling test until exhaustion (GXT) in this order. Individual anaerobic threshold (IAT) as well as VO2max were determined from the GXT. All tests were conducted on one day with 2 h rest in-between and were performed on participants´ own bicycle (installed to a Cyclus2 ergometer). Coefficients of correlation between test results were determined using Pearson`s regression test. Additionally, to find the best combination of variables predicting TT performance and determining which percentage of TT results can be explained by results from the other tests, a multiple regression analysis with stepwise inclusion was carried out. Results: Overall TT performance was 65.7±3.5min with an average power output (P) of 236±38 W. Significant correlations of TT were found with GXT maximum P (Pmax, r=-0.83) and IAT (r=-0.78). When related to body weight, correlations for Pmax and IAT were still significant, yet lower (r=-0.63 and r=-0.74, respectively). No significant correlations were found between TT and VO2max (r=-0.37) and results from WIN (Pmax: r=-0.03; Pmean: r=-0.29). Multiple regression revealed the highest coefficient of determination for the estimation of TT when Pmax and body weight were combined in one equation (R²=0.73, SEE=312s, F=28.8). Discussion: The results suggest that the Pmax in an incremental cycling test is the best predictor for performance in a 40km TT. In combination with the body weight approximately 73% of TT performance can be explained. Furthermore, in trained cyclists absolute power output seems to be a better predictor than VO2max and power output in relation to body weight. This is not surprising given that body weight can be fully invested into power output whereas it is carried by the bicycle frame. Results of the Wingate test do not seem to be relevant predictors for TT performance, possibly because endspurt does not influence overall performance relevantly enough.